Elevated myocardial oxygen consumption during cutaneous cold stress in young adult overweight and obese Africans - Toyib Olaniyan; Lawrence A. Olatunji (AOSIS, 2015)
Exaggerated sympathetic-mediated cardiovascular responses to stressful stimuli (such as cold exposure) has been linked to the development of hypertension and cardiovascular disease, which in turn has been demonstrated to predict the development of future hypertension. The aim of the present study was to test the hypothesis that enhanced change in myocardial oxygen consumption (MVO2) to cutaneous cold stress may be one potential mechanism that predisposes overweight/obese individuals in Africa to developing hypertension. The Rate-Pressure-Product (a non-invasive determinant of MVO2) was measured in normotensive young individuals aged between 18 and 25 years at baseline and during sympathetic activation elicited by cutaneous cold stimulation (CCS). Following CCS, there was a significant enhanced rate pressure product (RPP) change in overweight individuals (P=0.019). Furthermore, multivariate regression analysis showed that body mass index, but not body weight had a significant influence on RPP variation following CCS. Thus, it can be concluded that normotensive overweight or obese individuals have an exaggerated RPP response to the CCS. However, exposure to cold may augment sympathetic reactivity in overweight/obese individuals, which may contribute to increased risk of developing myocardial dysfunction, even in young normotensive individuals.